Venus observed - Fry, Christopher (London : Geoffrey cumberlege, 1954)
Olney Theatre, Players Incorporated presents Christopher Fry's "Venus Observed," with Margaret Phillips and Bramwell Fletcher, directed by Edgar L. Kloten, settings and lighting by James Waring, costumes by Joseph Lewis.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: English comedy; Theater programs -- Maryland -- Olney; Theater programs -- 1954.